Fundamentals of cancer prevention - Hess, Lisa M.; Alberts, David (Springer Berlin Heidelberg, 2014)
This authoritative work is an essential reference guide and tool for oncologists, primary care physicians, the research community, and students with an interest in reducing the burden of cancer. Written as a collaborative work by nationally recognized leaders in the field of cancer prevention and control, the third edition provides readers with new information related to recent developments in the field. The scope of this edition has been expanded to include topics related to global health and to provide readers with novel insights into the expanding disciplines within cancer prevention and control.